1996
DOI: 10.1097/00000539-199610000-00017
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Solution Concentration and Epinephrine on Lateral Distribution of Hyperbaric Tetracaine Spinal Anesthesia

Abstract: In a search of a differential spinal block between dependent and nondependent sides, we investigated whether the use of a larger concentration of hyperbaric tetracaine (T) and/or the omission of epinephrine (E) would provide differential spread in patients left for 15 min in the lateral decubitus position. Spinal anesthesia was performed in the lateral decubitus position with the operated side dependent in 60 patients scheduled for lower limb surgery. All patients remained lateral for 15 min after spinal injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Iselin-Chaves et al 17 reported no cases of unilateral spinal anaesthesia when injecting 12 mg hyperbaric tetracaine at high speeds through a Quincke needle, and showed that the use of a higher anaesthetic concentration did not provide clinical advantages in the unilateral distribution of spinal block. Our results confirmed this finding, but also demonstrated that directional spinal needles and relatively small doses of local anaesthetic provided successful unilateral spinal anaesthesia in up to 60% of cases 30 min after patients were turned to the supine position.…”
Section: Discussionmentioning
confidence: 99%
“…Iselin-Chaves et al 17 reported no cases of unilateral spinal anaesthesia when injecting 12 mg hyperbaric tetracaine at high speeds through a Quincke needle, and showed that the use of a higher anaesthetic concentration did not provide clinical advantages in the unilateral distribution of spinal block. Our results confirmed this finding, but also demonstrated that directional spinal needles and relatively small doses of local anaesthetic provided successful unilateral spinal anaesthesia in up to 60% of cases 30 min after patients were turned to the supine position.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that strict unilateral spinal block chance was increased with the use of an "air buffered technique. (10) We have decided to use 1.3 ml of heavy bupivacaine for unilateral anaesthesia in point of previous studies (6,16). We have also decided to use 10 mg of meperidine for two reasons; a) it was shown that 10 mg of meperidine was effective to prolong sensory block time in conventional spinal anaesthesia (9), b) high doses of meperidine would also increase the final volume of drug mixture and finally decrease the chance of strict unilateral block.…”
Section: Discussionmentioning
confidence: 99%
“…This technique provides high haemodynamic stability, fast recovery from anaesthesia, and high patient satisfaction (2)(3)(4). Studies showed that successful unilateral anaesthesia mostly depend on low dose of the local anaesthetic used and longstanding lateral decubitus position (5)(6). Although early recovery from spinal anaesthesia is an advantage of unilateral spinal anaesthesia, it may also be disadvantageous because pain may start earlier and spinal anaesthesia may not last long enough for surgery when surgery prolongs.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos autores preferem a agulha ponta de lápis por direcionar o fluxo do anestésico com objetivo de produzir raquianestesia unilateral 1,5,9, [14][15][16] . Entretanto, outros 2,11,17,18 preferem a agulha ponta cortante (Quincke) pelo potencial perigo da injeção lenta em sentido caudal proporcionar altas concentrações de anestésicos hiperbáricos. A agulha tipo Quincke proporciona um rápido aparecimento do LCR 19 , não causa má distribuição do anestésico local 13 e cursa com baixa incidência de cefaléia 20 .…”
Section: Discussionunclassified
“…Several authors prefer pencil point needles to orient anesthetic flow and thus help promoting unilateral spinal anesthesia 1,5,9, [14][15][16] . Others 2, 11,17,18 , however, prefer cutting point needles (Quincke) for the potential danger of slow caudal injection producing high hyperbaric anesthetic concentrations. Quincke needles allow a fast CSF return 19 , do not lead to local anesthetic mal-distribution 13 and are associated to low headache incidence 20 .…”
Section: Discussionmentioning
confidence: 99%